Ornithine Decarboxylase in Macrophages Exacerbates Colitis and Promotes Colitis-Associated Colon Carcinogenesis by Impairing M1 Immune Responses - Singh, Kshipra (Cancer Res, 2018)
Ornithine decarboxylase (ODC) is the rate-limiting enzyme for polyamine biosynthesis and restricts M1 macrophage activation in gastrointestinal (GI) infections. However, the role of macrophage ODC in colonic epithelial-driven inflammation is unknown. Here we investigate cell-specific effects of ODC in colitis and colitis-associated carcinogenesis (CAC). Human colonic macrophages expressed increased ODC levels in active ulcerative colitis and Crohn’s disease, colitis-associated dysplasia, and CAC. Mice lacking Odc in myeloid cells (Odc(Δmye) mice) that were treated with dextran sulfate sodium (DSS) exhibited improved survival, body weight, and colon length and reduced histologic injury versus control mice. In contrast, gastrointestinal epithelial-specific Odc knockout had no effect on clinical parameters. Despite reduced histologic damage, colitis tissues of Odc(Δmye) mice had increased levels of multiple pro-inflammatory cytokines and chemokines and enhanced expression of M1, but not M2 markers. In the azoxymethane (AOM)-DSS model of CAC, Odc(Δmye) mice had reduced tumor number, burden, and high-grade dysplasia. Tumors from Odc(Δmye) mice had increased M1, but not M2 macrophages. Increased levels of histone 3, lysine 9 acetylation (H3K9ac), a marker of open chromatin, were manifest in tumor macrophages of Odc(Δmye) mice, consistent with our findings that macrophage ODC affects histone modifications that upregulate M1 gene transcription during GI infections. These findings support the concept that macrophage ODC augments epithelial injury-associated colitis and CAC by impairing the M1 responses that stimulate epithelial repair, antimicrobial defense, and anti-tumoral immunity. They also suggest that macrophage ODC is an important target for colon cancer chemoprevention.